2022
DOI: 10.1111/acer.14908
|View full text |Cite
|
Sign up to set email alerts
|

Development and preliminary effectiveness of a smartphone‐based, just‐in‐time adaptive intervention for adults with alcohol misuse who are experiencing homelessness

Abstract: Background Adults experiencing homelessness have much higher rates of alcohol misuse than housed individuals. This study describes the development and preliminary effectiveness of a smartphone‐based, just‐in‐time adaptive intervention (JITAI) to reduce alcohol use among adults experiencing homelessness. Methods We conducted a pilot trial (N = 41; mean age [SD] = 45.2 [11.5]; 19.5% women) of the Smart‐T Alcohol JITAI where participants completed brief ecological momentary assessments (EMAs) each day, received p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Thus, motivation may appropriately decrease over a follow‐up period, or an individual may experience an unsuccessful change attempt and a concomitant reduction in motivation due to discouragement. For example, a recent effectiveness trial among adults experiencing homelessness showed that a motivation‐guided, just‐in‐time intervention delivered via ecological momentary assessment reduced drinking (Walters et al, 2022), suggesting how changing motivation could be utilized to provide a tailored, repeated intervention. Assessing and responding to motivation as a dynamic variable rather than a static indicator of individual differences may help our understanding of how interventions change motivation and, ultimately, drinking behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, motivation may appropriately decrease over a follow‐up period, or an individual may experience an unsuccessful change attempt and a concomitant reduction in motivation due to discouragement. For example, a recent effectiveness trial among adults experiencing homelessness showed that a motivation‐guided, just‐in‐time intervention delivered via ecological momentary assessment reduced drinking (Walters et al, 2022), suggesting how changing motivation could be utilized to provide a tailored, repeated intervention. Assessing and responding to motivation as a dynamic variable rather than a static indicator of individual differences may help our understanding of how interventions change motivation and, ultimately, drinking behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this work is the first attempt to go beyond the detection of BDEs and predict imminent BDEs using the combination of smartphone sensor data and ML coupled with XAI for enhancing the explainability of the algorithms. The prediction model of BDEs combines ML and XAI toward the ultimate goal of supporting JITAIs to prevent BDEs [2,[32][33][34].…”
Section: Study Objectives and Noveltymentioning
confidence: 99%
“…The state of being homeless is important because people who experience it can be at increased risk of adverse outcomes compared to their peers who do not, especially those experiencing long-term and repeated homelessness [12,13]. Individuals who experience homelessness may have complex health care needs [14][15][16][17][18]. Homeless individuals are at greater risk of death, hospital admission related to substance use, and poor mental and physical health [14][15][16]19,20].…”
Section: Overviewmentioning
confidence: 99%